2012
DOI: 10.1016/j.neuropsychologia.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia structures differentially contribute to verbal fluency: Evidence from Human Immunodeficiency Virus (HIV)-infected adults

Abstract: Background The basal ganglia (BG) are involved in executive language functions (i.e., verbal fluency) through their connections with cortical structures. The caudate and putamen receive separate inputs from prefrontal and premotor cortices, and may differentially contribute to verbal fluency performance. We examined BG integrity in relation to lexicosemantic verbal fluency performance among older HIV infected adults. Method 20 older (50+ years) HIV+ adults underwent MRI and were administered measures of sema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
(51 reference statements)
6
26
0
Order By: Relevance
“…searching within a given field like house pets, and then switching to a new field like aquatic animals (Troyer et al, 1998), a deficit at this level induced by lesions to the basal ganglia could also account for our VLSM results (e.g. Troyer et al, 2004;Abutalebi et al 2009;Thames et al, 2012).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…searching within a given field like house pets, and then switching to a new field like aquatic animals (Troyer et al, 1998), a deficit at this level induced by lesions to the basal ganglia could also account for our VLSM results (e.g. Troyer et al, 2004;Abutalebi et al 2009;Thames et al, 2012).…”
Section: Discussionmentioning
confidence: 66%
“…In the ganglia-thalamo-cortical loops, the DLPFC is connected to the dorsolateral caudate nucleus and the internal globus pallidus. Fluency impairments following basal ganglia disruption have notably been demonstrated in clinical studies on HIV (Thames et al, 2012), as well as in Huntington and Parkinson patients (Lawrence et al, 1998;Benke et al, 2003), and might follow from a disruption of the maintenance, monitoring and selection of goalrelevant representations by prefrontal cortices (Wagner et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…28 In a study of HIV dementia, significant correlation was found between caudate volumes and phonemic word generation, whereas performance on phonemic switching predicted putamen volume. 29 In ALS, impaired verbal fluency is regarded as one of the earliest and most prevalent of neuropsychological deficits. 30 While the size of our study group is underpowered to make meaningful comparative neuropsychological Vertex-wise thalamic differences between C9orf72-positive and -negative patients with ALS (p < 0.05, corrected)…”
Section: Resultsmentioning
confidence: 99%
“…With regard to neural networks, phonemic fluency is neuroanatomically associated with the left inferior frontal gyrus (IFG), whereas semantic/category fluency has been linked to the superior temporal gyrus (Prince, Tsukiura, & Cabeza, 2007; Sherman & Massman, 1999). The basal ganglia (BG), preferentially targeted by HIV infection, have also been implicated in verbal fluency tasks, with reduced caudate volume significantly predicting lower phonemic fluency performance in an HIV+ sample (Thames et al, 2012). fMRI studies of HIV− samples have reported BG involvement (Fu, Morgan, Suckling, Williams, Andrew, Vythelingum, & McGuire, 2002; Wagner, Sebastian, Lieb, Tüscher, Tadić, 2014) when individuals perform executive-mediated language tasks (e.g., word generation), suggesting that the BG play a key role in lexical retrieval outside of HIV infection.…”
Section: Introductionmentioning
confidence: 99%